Ethnic influences on the perceptual properties of human chemosignals - Parma, Valentina (2019)
Individuals of African and Caucasian descent show different chemical signatures in their body odors (BO). Does such biological difference have a perceptual correlate? We tested BO donors and raters of Afro-Portuguese (AP) and Caucasian (C) descent to investigate whether olfactory ratings reveal an ethnic bias and whether olfactory ethnic discrimination is possible. C (vs. AP) women rated the C BO as more pleasant, even when controlling for intensity. The C BO labelled as AP was rated as more intense by C raters. Although discriminability of ethnicity and sex is at chance, a nominal advantage for AP vs. C BO emerges.